Knowledge and attitude of senior staff nurses regarding geriatrics health care in a tertiary public hospital - Mahmud, Md Shohel; Begum, Most Khadija; Akhter, Jabin (Asian Journal of Medical and Biological Research, 2020)
There is proportionate increase in the health problems along with increase in geriatric population in Bangladesh. Nurses need to be well equipped with knowledge and should also have a positive attitude regarding geriatric care. The current cross sectional study conducted with an aim to assess the knowledge and attitude of senior staff nurses and associated factors regarding geriatrics health care. This cross-sectional study was conducted among 384 nurses working at a tertiary public hospitals in the Rangpur city of Bangladesh from January 2019 to December, 2019. Participants were selected using simple random sampling from the list of staff. The Kogan's attitude questionnaire was used to measure nurses' attitudes toward the elderly. Out of 384 respondents, 36.5% were of age group 21-30 years, most of female (84.4%) and married (85.2%) with maximum Muslim (88.5%) religious view. About half of the respondents had diploma level education (53.9%) and having 1-5 years job experience (48.7%). 64.1% respondents have monthly income within BDT 25001-35000. 35.4% of the nurses agreed for skill nursing and 36.5% agreed for challenging and stimulating nursing care, and 54.2% nurses agree for need highly skilled nursing. Most (97.7%) of the nurses opined needs special geriatric wards for effective care and 93.8% requires special training. According to Kogan attitudes scale, 36.2% nurse had negative attitudes and 63.8% had positive attitudes regarding geriatric health care. More than one third (38.5%) of respondents were average knowledge; followed by 32.8% respondents were good knowledge. There is a statistically significant relationship present between job experience and attitude (λ2=26.193, p<0.05) and job experience and knowledge (λ2=15.04, p<0.04) of nurses. It was concluded that senior staff nurses had average knowledge and positive attitude regarding geriatric care. Asian J. Med. Biol. Res. September 2020, 6(3): 431-439